ENVIRONMENTAL PSYCHOLOGY: पर्यावरणीय मनोविज्ञान - Hemlata (International Journal of Research -GRANTHAALAYAH, 2015)
There is a multidisciplinary field focused on the study of the interrelations of human and its environment. Here, the broad definition of the word 'Environment' (item antecedent) includes all of the natural environment, social environment, built environment, educational environment and information environment. Over the years, extensive research work has been done on various aspects of the environment and this subject is gradually becoming a prosperity study area, many subjects have contributed to this study. Under its study area, the type of environment, the attitude of man towards them, the effects of culture, the structure and design of environment etc. are being analyzed in detail. मानव एवं उसके पर्यावरण के अन्तर्सम्बन्धों के अध्ययन पर केन्द्रित एक बहुविषयी क्षेत्र है। यहाँ पर पर्यावरण ;मदअपतवदउमदजद्ध शब्द की वृहद परिभाषा में प्राकृतिक पर्यावरणए सामाजिक पर्यावरणए निर्मित पर्यावरणए शैक्षिक पर्यावरण तथा सूचना.पर्यावरण सब समाहित हैं। विगत वर्षों में पर्यावरण के विभिन्न पक्षों को लेकर व्यापक शोध कार्य हुए हैं और यह विषय क्रमशः एक समृद्धि अध्ययन क्षेत्र बनता जा रहा है इस विषय में अध्ययन में अनेक विषयों का योगदान रहा है। इसके अध्ययन क्षेत्र के अन्तर्गत वातावरण के प्रकारए उनकेए प्रति मनुष्य की अभिवृत्तिए संस्कृति के प्रभावए पर्यावरण की संरचना और अभिकल्प इत्यादि का विस्तृति विश्लेषण किया जा रहा है।